Modeling of the Electrical Characteristics and Degradation Mechanisms of UV-C LEDs - Nicola Roccato; Francesco Piva; Carlo De Santi; Matteo Buffolo; Normal Susilo; Daniel Hauer Vidal; Anton Muhin; Luca Sulmoni; Tim Wernicke; Micheal Kneissl; Gaudenzio Meneghesso; Enrico Zanoni; et al. (IEEE Photonics Journal)
In this paper we investigate the reliability of AlGaN-based UV-C LEDs with an emission wavelength of 265 nm. By submitting the devices to constant current stress, two main electrical degradation processes are identified: a turn-on voltage shift and an increase in the forward leakage current. In particular, these processes were respectively attributed to: (i) a partial passivation of the Mg-doping concentration in the region adjacent to the contact, probably caused by a local hydrogen diffusion, and ii) a diffusion/generation process of defects in the interlayer, responsible for the increase in the trap-assisted tunneling. To validate these hypotheses, we employed TCAD simulations by varying only the Mg-doping concentration in the region adjacent to the p-contact and the defect density in the interlayer. Thus, we correctly reproduced the experimental variation in electrical characteristics, confirming the physical mechanisms identified.